Long-term effectiveness of inpatient and day hospital treatment in departments of psychosomatic medicine and psychotherapy in Germany - Kessler, Henrik; Doering, Stephan; Kehyayan, Aram; Pape, Magdalena; Hofmann, Tobias; Rose, Matthias; Imbierowicz, Katrin; Geiser, Franziska; Croy, Ilona; Weidner, Kerstin; Rademacher, Jörg; Michalek, Silke; et al. (Frontiers in Psychiatry, 2025)
BackgroundThere is a lack of reliable data concerning the long-term effectiveness of psychosomatic inpatient and day hospital treatment in a naturalistic setting. The Multicenter Effectiveness Study of Inpatient and Day Hospital Treatment in Departments of Psychosomatic Medicine and Psychotherapy in Germany aims to provide such data. The study itself and effectiveness from admission to discharge have already been reported in this journal (Doering et al., 2023). This brief report adds 12-month follow-up data.MethodsThe relevant outcome variables concerning somatoform, trauma-related, eating and personality disorders, as well as anxiety and depressive disorders were assessed by means of questionnaires on admission (T0), at discharge (T1) and after 12 months (T2). In order to make targeted statements about effectiveness regarding only clinically relevant symptoms, each symptom domain was stratified by severity at admission.ResultsFrom a total of 2,094 patients at admission, 60.6% still provided data at T2. Overall, the changes achieved at discharge (T1) already reported in Doering (2023) remained stable over the 12-month follow-up period (T2). There were hence significant improvements from T0 to T2 across all symptom domains with large effect sizes ranging from d=1.0 to 3.4.ConclusionsThe already reported effectiveness of inpatient and day hospital treatment in German university departments of Psychosomatic Medicine and Psychotherapy in a naturalistic setting is further strengthened by providing evidence for sustained treatment effects over the 12-month follow-up period. Importantly, the entire spectrum of disorders investigated showed this pattern.Clinical Trial Registrationhttps://drks.de/search/de/trial/DRKS00016412 RKS00016412, identifier DRKS00016412.